Efficacy and safety of the biosimilar ABP 501 compared with adalimumab in patients with moderate to severe rheumatoid arthritis: a randomised, double-blind, phase III equivalence study. Issue 10 (5th June 2017) - Cohen, Stanley; Genovese, Mark C; Choy, Ernest; Perez-Ruiz, Fernando; Matsumoto, Alan; Pavelka, Karel; Pablos, Jose L; Rizzo, Warren; Hrycaj, Pawel; Zhang, Nan; Shergy, William; Kaur, Primal
Abstract : Objectives: ABP 501 is a Food and Drug Administration-approved biosimilar to adalimumab; structural, functional and pharmacokinetic evaluations have shown that the two are highly similar. We report results from a phase III study comparing efficacy, safety and immunogenicity between ABP 501 and adalimumab. Methods: In this randomised, double-blind, active comparator-controlled, 26-week equivalence study, patients with moderate to severe active rheumatoid arthritis (RA) despite methotrexate were randomised (1:1) to ABP 501 or adalimumab (40 mg) every 2 weeks. Primary endpoint was risk ratio (RR) of ACR20 between groups at week 24. Primary hypothesis that the treatments were equivalent would be confirmed if the 90% CI for RR of ACR20 at week 24 fell between 0.738 and 1.355, demonstrating that ABP 501 is similar to adalimumab. Secondary endpoints included Disease Activity Score 28-joint count-C reactive protein (DAS28-CRP). Safety was assessed via adverse events (AEs) and laboratory evaluations. Antidrug antibodies were assessed to determine immunogenicity. Results: A total of 526 patients were randomised (n=264, ABP 501; n=262 adalimumab) and 494 completed the study. ACR20 response at week 24 was 74.6% (ABP 501) and 72.4% (adalimumab). At week 24, the RR of ACR20 (90% CI) between groups was 1.039 (0.954, 1.133), confirming the primary hypothesis. Changes from baseline in DAS28-CRP, ACR50 and ACR70 were similar. There were no clinically meaningful differences in AEs and laboratory abnormalities. A total of 38.3% (ABP 501) and 38.2% (adalimumab) of patients tested positive for binding antidrug antibodies. Conclusions: Results from this study demonstrate that ABP 501 is similar to adalimumab in clinical efficacy, safety and immunogenicity in patients with moderate to severe RA. Trial registration number: NCT01970475; Results.